Empowering Leadership and Employee Loyalty in the Hospitality Industry: The Mediating Effects of Job Satisfaction and Organizational Commitment - Nurhasanah, Siti; Shafira Arifiani, Ratya; Ramadhani Fuadiputra, Iqbal (Jurnal Ilmu Manajemen, 2026)
The hospitality industry is characterized by intense competition and a high level of employee turnover, making effective leadership essential for enhancing employee loyalty. This study aims to investigate the relationship between empowering leadership and employee loyalty in the hospitality industry, as well as to examine the mediating roles of job satisfaction and organizational commitment in this relationship. Using a quantitative approach with a survey design, data were collected from 170 hotel employees across several major cities in Indonesia through a structured questionnaire. Data analysis was conducted using Hayes’ (2018) PROCESS Macro for SPSS version 3.0, employing Model 4 to test a parallel multiple mediation model. The findings reveal that empowering leadership has a significant positive effect on employee loyalty. Furthermore, job satisfaction and organizational commitment are found to partially mediate the relationship between empowering leadership and employee loyalty. Specifically, empowering leadership significantly and positively influences both job satisfaction and organizational commitment, and these two mediators, in turn, significantly and positively affect employee loyalty. These results underscore the importance of adopting empowering leadership practices to foster employee retention and strengthen loyalty in the hospitality sector. Organizations seeking to reduce turnover and enhance long-term workforce stability should prioritize leadership approaches that empower employees while simultaneously cultivating positive psychological conditions, particularly job satisfaction and organizational commitment.